Decision Support System for Employee Bonus Recommendation Using Fuzzy Logic - Ardhiansyah, Alfian; Sudarni, Ajeng Rahma; Khaira, Mulil; Prasetyo, Septian Eko (Journal Sensi: Strategic of Education in Information System, 2025)
A decision support system is indeed something that should be used to make it easier for organizations to determine a policy. With the existence of information technology, all data analysis and calculation is carried out automatically through computers. Similarly, in making recommendations to give bonuses to an employee in a company or institution. To speed up the decision-making process, a system is needed that can provide recommendations like calculations made by human intelligence. The system was developed using the fuzzy logic method that expresses classical logic into linguistic forms. The advantage offered by this logic is that it produces a more just and humane decision such as a decision that results from human feelings and thoughts. This system uses four variables used to determine the receipt of bonus wages, namely the age of the employee, the length of service, the amount of salary and productivity in one month. Each of these variables has a linguistic variable that is used to represent a certain state or condition that utilizes natural language. This research produces a system that can provide recommendations for organizations or companies to use in determining the receipt of bonus wages in accordance with the rules applied.